Implementation Of Patient Safety By Nurses In Bina Kasih Hospital, Pekanbaru City: Penerapan Patient Safety Oleh Perawat Di Rumah Sakit Bina Kasih Kota Pekanbaru - Rizki Putri Utami; Zulmeliza Rasyid; Endang Purnawati Rahayu (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
The application of patient safety for nurses is very important in an effort to reduce Patient Safety Incidents (IKP), from the Hospital Patient Safety Committee (KKP-RS) team regarding Patient Safety Incidents (IKP) and there are still 6 cases that have sprung up in 2021 such as Unexpected Events (KTD) 1 case, Non Injury Event (KTC) 2 cases, Near Injury Event (KNC) 2 cases, and Potential Injury Event (KPC) 1 case. The purpose of this study was to determine the relationship between the frequency distribution of the application of patient safety by nurses. This research is quantitative analysis using a cross sectional design with 45 nurses at Bina Kasih Hospital Pekanbaru City. Data analysis was performed univariate and bivariate with chi-square test (α=0.05). The results of the bivariate analysis showed that there was a significant relationship between knowledge p value = 0.001, attitude p value = 0.001, motivation p value = 0.005, working period p value = 0.002 patient safety by nurses. The results of the study concluded that there was a relationship between knowledge, attitude, motivation, patient safety working period by nurses. It is recommended to the hospital, especially to the head of the K3 section to be able to carry out K3RS properly by providing education to nurses who are in direct contact with patients.